Synthetic adipic complex tetraesters as eco‐friendly lubricants. (12th April 2013) - Mirci, Liviu E.; Pătrut, Alina
ABSTRACT The paper presents results concerning the synthesis and characterisation as lubricants with biodegradability potential of some complex tetraesters realised on the basis of adipic acid and different glycols such as (mono) ethylene, 1, 3‐propylene, 1, 4‐butylene, 1, 5‐pentamethylene, 1, 6‐hexamethylene, diethylene and triethylene glycol, respectively, along with oleic acid used, considered as an end, final segment or as a capping element. On the basis of a regular alternation or successive distribution principle of the polar and nonpolar chemical functions equally distributed, shared out on the length of a sufficient, satisfactorily long, large molecule, valuable synthetic complex tetraester lubricants considered as eco‐friendly base oils with biodegradability potential were performed. These products showed very good tribological properties, such as high viscosity indices and high flash points, and also very good lubricity features. Copyright © 2013 John Wiley & Sons, Ltd.